NMR spectroscopy explained : - Jacobsen, Neil E. (Wiley-Interscience, 2007)
NMR Spectroscopy Explained : Simplified Theory, Applications and Examples for Organic Chemistry and Structural Biology provides a fresh, practical guide to NMR for both students and practitioners, in a clearly written and non-mathematical format. It gives the reader an intermediate level theoretical basis for understanding laboratory applications, developing concepts gradually within the context of examples and useful experiments.